Gene-by-environment interaction: study designs and analytical methods - Cupples, L. Adrienne (Henry Stewart Talks, 2007)
Study designs that evaluate the joint effects of gene-by-environment interactions, including case-control, case only, matched pairs, random samples and family studies, Distinguishing between gene-by-environment interaction and genetic heterogeneity, Description of analytical procedures and effect measures for evaluation of gene-by-environment interaction for dichotomous and continuous outcomes, Case-control, case only, ordered subset, variance component and PBAT analyses